A regulated multiple-output high-voltage charge pump IC for implantable neural stimulators. (October 2019) - Abdi, Alfian; Cha, Hyouk-Kyu
Abstract: In this paper, a single-input multiple-output high-voltage charge pump integrated circuit (IC) for neural stimulation applications is presented. The proposed circuit, implemented using 0.18-μm standard low-voltage CMOS process, reliably generates three high-voltage outputs of 12.8 V, 9.6 V, and 6.4 V from a single 2.8 V-input source while regulating the output with load current up to 1 mA. In addition, an input voltage modulated regulation scheme is employed for good efficiency and regulation performance. The designed IC, which includes three charge pump cores and regulation circuits, occupies 0.8 mm 2 of core die area.